(3QhM GdQhM ajeG MOK HYO GdeGFI GdJGSYI ef GdaJf hGdaJhMs - (3YjSi Hf dWa Gddg Hf GdeWgQ Hf GdeJhcd Ydj Gddg jMji TQa GdOjf Gdjefis
(3ChdgG (B:s
(3NdJ SfI KdGKdGjf hCda s
(3BNQgG (B:s
(3hEdi gGgfG GfJgi GdLRA GdKGdK ef QhM GdQhM hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B402 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B550 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B207 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(284(3O(B) s
Keywords: (3GdJGQjNs